Copy number variations in the amylase gene (AMY2B) in Japanese native dog breeds. (11th September 2015) - Tonoike, A.; Hori, Y.; Inoue‐Murayama, M.; Konno, A.; Fujita, K.; Miyado, M.; Fukami, M.; Nagasawa, M.; Mogi, K.; Kikusui, T.
Summary A recent study suggested that increased copy numbers of the AMY2B gene might be a crucial genetic change that occurred during the domestication of dogs. To investigate AMY2B expansion in ancient breeds, which are highly divergent from modern breeds of presumed European origins, we analysed copy numbers in native Japanese dog breeds. Copy numbers in the Akita and Shiba, two ancient breeds in Japan, were higher than those in wolves. However, compared to a group of various modern breeds, Akitas had fewer copy numbers, whereas Shibas exhibited the same level of expansion as modern breeds. Interestingly, average AMY2B copy numbers in the Jomon‐Shiba, a unique line of the Shiba that has been bred to maintain their appearance resembling ancestors of native Japanese dogs and that originated in the same region as the Akita, were lower than those in the Shiba. These differences may have arisen from the earlier introduction of rice farming to the region in which the Shiba originated compared to the region in which the Akita and the Jomon‐Shiba originated. Thus, our data provide insights into the relationship between the introduction of agriculture and AMY2B expansion in dogs.